Clinical pharmacists’ role in identification of drug related problems in a teritiary care teaching hospital (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
ObjectiveTo evaluate the drug related problems in which it occurs mostly in both IP and OP. To examine the nature, frequency and to estimate the risks associated with drug related problems in a General Medicine Department.MethodologyA prospective observational study was carried out at a 750 bedded teaching hospital for a period of 6 months. Patients were enrolled on the basis of inclusion and exclusion criteria. The inclusion criterion involves patients in multiple drug therapy with a minimum of two drugs and patients of both sexes.ResultsA total of 508 cases were collected during the study period. Among them 165 cases due to the infectious diseases. The most common DRP is possible drug-drug interaction in part of patients i.e.219.Based on severity level, moderate drug-drug interactions were found to be maximum (48.8%) followed by minor (28.4%) and major 22.8%. Adverse drug reactions (ADRs) are the second major DRP found in 34 cases. Poly pharmacy is found to be the most important cause of DRPs followed by in appropriate drug choices, poor medication adherence risk. Statistical analysis was performed using spearman’s correlation test and it was found a significant difference (P=0.0001) between the drug related problems of inpatient and outpatient department.ConclusionClinical pharmacist as a member of the health care team can contribute significantly to the improved patient outcomes by monitoring drug therapy and can also promote rational use of drugs.